Consumption of manjakani among postpartum mothers and risk of heavy metal contamination - Ahmad Bustami, Normina; Ho, Yu Bin; Tan, Chung Keat; Aris, Ahmad Zaharin; Tan, Eugenie Sin Sing (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: In Malaysia, herbal medicines are used for variety of reasons including health promotion and home remedies during pregnancy and postpartum with Manjakani (Quercus infectoria) as one of the most commonly consumed herbs. Herbal medicines consumption had been linked to heavy metals contamination and transfer from mother to infant and may affect infant’s growth and development. This study aims to (i) determine Manjakani consumption among postpartum mothers, (ii) quantify its heavy metals level, namely lead, cadmium, arsenic and chromium, and (iii) determine health risk associated with its consumption. Methods: A cross-sectional study involving 106 postpartum mothers was carried out in Kuala Lumpur. Six samples of Manjakani were sampled and extracted using microwave digester and analysed using Inductively coupled plasma mass spectrometry (ICP-MS). Non-carcinogenic health risks for herbal medicine consumption were calculated using Hazard Quotient (HQ). Results: Manjakani was consumed by 16% of mothers (n=17). Highest level of the metals was shown by chromium with mean concentration of 4210 ± 1910 ug/kg, followed by lead (170.8 ± 193.2), arsenic (39.3 ± 27.1) and cadmium (7.7 ± 0.76). There were no significant non-carcinogenic health risks with lead, arsenic, chromium and cadmium contamination (HQ < 1). Conclusion: Manjakani is consumed by mothers during confinement period. Heavy metals were quantified in Manjakani although no significant association was observed with socio-demographic characteristics and birth outcomes.